Interstitial-mediated dislocation climb and the weakening of particle-reinforced alloys under irradiation - Thompson, D; Tarleton, E; Roberts, S; Fitzgerald, S (American Physical Society, 2018)
Dislocations can climb out of their glide plane by absorbing (or emitting) point defects [vacancies and self-interstitial atoms (SIAs)]. In contrast with conservative glide motion, climb relies on the point defects' thermal diffusion and hence operates on much longer timescales, leading to some forms of creep. While equilibrium point defect concentrations allow dislocations to climb to relieve nonglide stresses, point defect supersaturations also lead to osmotic forces, driving dislocation motion even in the absence of external stresses. Self-interstitial atoms typically have significantly higher formation energies than vacancies, so their contribution to climb is usually ignored. However, under irradiation conditions, both types of defect are athermally created in equal numbers. In this paper, we use simple thermodynamic arguments to show that the contribution of interstitials cannot be neglected in irradiated materials and that the osmotic force they induce on dislocations is many orders of magnitude larger than that caused by vacancies. This explains why the prismatic dislocation loops observed by in situ transmission electron microscope irradiations are more often of interstitial rather than vacancy character. Using discrete dislocation dynamics simulations, we investigate the effect on dislocation-obstacle interactions and find reductions in the depinning time of many orders of magnitude. This has important consequences for the strength of particle-reinforced alloys under irradiation.